ПСИХОАНАЛИТИЧЕСКИЙ ТРЕНИНГ КАК ИНСТРУМЕНТ РАЗВИТИЯ ПСИХОЛОГИЧЕСКИХ ГРАНИЦ ПОДРОСТКА (World Science, 2019)
The article is devoted to psychoanalytic training as an instrument for the development of psychological boundaries of adolescents. The base principles of the training are described and the features of its structure and duration are characterized. The topics that were put forward as the main ones for certain meetings of teenage groups are justified in detail. Psychoanalytic training has been studied in terms of its effectiveness and impact on the development of the boundaries as well as their structure and functions in adolescents. The analysis is conducted of all those mental changes and new growths due to which the formation of the boundaries of the personality takes place.